The Implementation of Policies that Supports the Creation of Creative Power or Soft Power from Creative Industries in Thailand: A Case Study of Foreign Movies Set and Shot in Thailand - Boonchan, Wimolwan; Srisorn, Wijittra (Suan Dusit Graduate School Academic Journal, 2026)
The study on the implementation of policies to support the creation of creative power or soft power from creative industries in Thailand: a case study of an international film production crew in Thailand aimed to 1) study the causes of the problems and obstacles from government policies preventing international film crews from choosing Thailand; 2) analyze the policy to support the creation of creative power or Soft Power from the creative industries in Thailand, a case study of an international film crew in Thailand, based on the theory of top-down policy implementation according to the concept of Van Meter and Van Horn; and 3) present guidelines for driving the policy to support the creation of creative power or Soft Power, a case study through international film crews in Thailand, to elevate and develop the knowledge and creativity of Thais. The research results found that 1) The reasons why foreign film crews did not choose Thailand were due to strict control of the film script, political conditions, and lack of coordination. 2) Regarding the results of policy implementation, the positive results were that the measure to promote foreign film crews in Thailand can generate income for the country and the local area, create a good image of Thailand, and can increase the potential to compete with competitors. 3) The guidelines for upgrading and developing the knowledge and creativity capabilities of Thais in the form of the SET Model were presented as follows: 1) Skill training and knowledge enhancement 2) Enhancing quality of life 3) Training to develop thinking methods, with the aim of presenting guidelines for the government sector to drive policies to support the creation of creative power or Soft Power from the creative industries in Thailand.